A population-based study of teenage marriage in Upper Egypt - Saleh, Lamiaa; Ashry, Hamada; Al-Fakharany, Reham S.; Abbas, Ahmed M.; Elbahrawe, Rasha S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Early marriage of teenage girls before the age of 18 is a serious problem concerning public health that perils the girls' childhood in developing countries. The current study aims to highlight the socioeconomic background and the adverse drawbacks of teenage marriage in Upper Egypt. Methods: A population-based, cross-sectional study was conducted on 962 married females who were selected randomly by using a multistage random sampling technique. The participants were attending four urban and four rural primary health care facilities in Beni-Suef governorate, Upper Egypt in the period between May 2018 and October 2018. An interviewing questionnaire was designed to detect the suspected socio-demographic factors associated with teenage marriage. Results: The mean age of marriage of the studied participants was 18.7±3.5 years. The study revealed that 50.8% of the studied population was 18 years or less at marriage versus 49.2% married at age more than 18. Also there is a significant difference between the age of marriage and the educational level of both husbands and wives (p<0.001). The rate of accidental hemorrhage (3% versus 1.4%), placenta previa (2.2 versus 0.6%), eclampsia (1.8% versus 0.4%), and intrauterine growth restriction (3% versus 0.6%) were significantly higher in those married before 18 years (p=0.028, 0.036, 0.038, 0.005, respectively). Conclusions: This study demonstrated a significant relationship between the marital age and the implicated socio-demographic determinants. Adverse sexual relationship and pregnancy outcomes were significantly related to the age of marriage.